Effectiveness of Health Educational Program on Nurse’s Practices toward Care of Neonates with Hypoglycemia at Neonatal Intensive Care Unit in Al-Nasiriya City - Hussein Oraibi Hawi; Suad Hassoon Khudhair (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: In the neonatal age, hypoglycemia is the most common metabolic disturbance. A common problem in newborn infant care is screening at-risk babies and controlling low blood glucose levels in the first hours to days of life.Methodology: A quasi- experimental design used in the present study with application of a (pre-test/ posttest I, post-test II), The study was carried out at NICU in teaching hospitals in Nasiriya city, Iraq (Bint Alhuda Teaching and Muhammed Al-Musawi Children Hospitals). The research sample includes (40) nurses working in NICU. They are selected by using non probability sampling (purposive sample). Results : The findings of the study in this table indicate that, according to the mean of the score level of assessment, there is low level of assessment of 40 (100%) at level (1-1.66) the mean of score and standard deviation are (1.25±0.087) at the pretest. There is high level of assessment of 40 (100%) at level (2.34-3) the mean of score and standard deviation are (2.54±0.097) at the posttest I. There is high level of assessment of 23 (82.5%) at level (2.34-3) the mean of score and standard deviation are (2.47±0.154) at the posttest II. the finding indicated that the improvement the nurses practice toward care neonates with hypoglycemia in the Posttest II .Conclusion: The program has effectiveness on the nurses’ level of practice toward neonatal hypoglycemia during the 2 period of test, the study group have low level of practice before implementation of an educational program and the level of practice ascend to high level at posttest I and stay in high level at posttest II. There is a significant deference between the means of the nurses practice before and after implementation of the program.Recommendation: The researcher suggests that nurses’ practices be assessed on a regular basis to identify any flaws that may be affecting their care of neonates with hypoglycemia. The importance of fully utilizing continuing medical education to provide neonatal hypoglycemia courses for all NICU nurses